Global, regional, and national burden of diabetes from 1990 to 2021, with projections of prevalence to 2050: a systematic analysis for the Global Burden of Disease Study 2021 - Ong, Kanyin Liane (ELSEVIER SCIENCE INC, 2024)
10.1016/S0140-6736(23)01301-6